Itch in Allergic Contact Dermatitis - Lambert, Julien (Frontiers in Allergy, 2021)
Contact dermatitis is a continuous growing environmental and occupational health problem. It results in high costs for health care systems and the economy due to productivity loss. Moreover, it has a huge impact on the quality of life of patients. The immune response to contact allergy is very complex and not totally elucidated. Recently unique pathways preferentially activated by different allergens were identified. As for a lot of chronic itch disorders, antihistamines are ineffective for allergic contact dermatitis, suggesting a non-histaminergic itch. The precise mechanisms that underlie the development of itch in ACD remain poorly defined. This short review addresses the most recent insights in pruritus in ACD, opening perspectives for future therapies.